Investigation of the Chemical Composition, Microstructure, Density, Microhardness, and Elastic Modulus of the New β Ti-50Nb-xMo Alloys for Biomedical Applications - Martins Junior, José Roberto Severino (2024)
β-type titanium alloys with a body-centered cubic structure are highly useful in orthopedics due to their low elastic modulus, lower than other commonly used alloys such as stainless steel and Co-Cr alloys. The formation of the β phase in titanium alloys is achieved through β-stabilizing elements such as Nb, Mo, and Ta. To produce new β alloys with a low modulus of elasticity, this work aimed to produce our alloy system for biomedical applications (Ti-50Nb-Mo). The alloys were produced by arc-melting and have the following compositions Ti-50Nb-xMo (x = 0, 3, 5, 7, and 12 wt% Mo). The alloys were characterized by density, X-ray diffraction, scanning electron microscopy, microhardness, and elastic modulus. It is worth highlighting that this new set of alloys of the Ti-50Nb-Mo system produced in this study is unprecedented; due to this, there needs to be a report in the literature on the production and structural characterization, hardness, and elastic modulus analyses. The microstructure of the alloys has an exclusively β phase (with bcc crystalline structure). The results show that adding molybdenum considerably increased the microhardness and decreased the elastic modulus, with values around 80 GPa, below the metallic materials used commercially for this type of application. From the produced alloys, Ti-50Nb-12Mo is highlighted due to its lower elastic modulus.